Perlindungan Hukum Terhadap Anak Dari Konten Berbahaya Dalam Media Cetak Dan Elektronik - Evi Deliana HZ (Jurnal Ilmu Hukum, 2013)
Children are the hope of the nation which is the next generation, where the future of this nation eventually will be placed. As the successor to the nation, then the current generation obligation to provide protection to the They of the moral damage caused by the use of harmful content in the print and electronic media, especially those containing elements of violence and pornograph. Regulations governing the legal protection of children from harmful content in the print and electronic media are still common, there are no specific rules intended to give legal protection of children from harmful content that may be present in the print and electronic media.